Analysis of technical problems in modern super-slim high-rise residential buildings - Szołomicki, Jerzy; Golasz-Szołomicka, Hanna (Budownictwo i Architektura / Civil and Architectural Engineering, 2021)
The purpose of this paper is to present a new skyscraper typology which has developed over the recent years – super-tall and slender, needle-like residential towers. This trend appeared on the construction market along with the progress of advanced structural solutions and the high demand for luxury apartments with spectacular views. Two types of constructions can be distinguished within this typology: ultra-luxury super-slim towers with the exclusivity of one or two apartments per floor (e.g. located in Manhattan, New York) and other slender high-rise towers, built in Dubai, Abu Dhabi, Hong Kong, Bangkok, and Melbourne, among others, which have multiple apartments on each floor. This paper presents a survey of selected slender high-rise buildings, where structural improvements in tall buildings developed over the recent decade are considered from the architectural and structural view.